IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY PT. PERTAMINA (PERSERO) REFINERY UNIT II DUMAI UNTUK PENINGKATAN TARAF HIDUP MASYARAKAT - Rezky Aditya Suryani (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
ABSTRACT This study aims to to know the implementation of their corporate social responsibility PT. Pertamina (Persero), refinery Dumai unit II to improve the life quality of society. The theory harold lasswell was used in the study that provides the delivery of messages by a communicator to communicant through a medium that give rise to a certain effect. The kind of research that is used is a method of descriptive with the qualitative analysis. The technique of the data collection was done through observation, interview and study literature available. Analysis technique data using triangulation. The results of the interview presented in the form of a question and answer session and a picture (a photograph). The results of the interviews data analyzed by review all data and the presentation of data. This research result indicates that the implementation of corporate social responsibility PT. Pertamina (Persero) refinery Dumai unit II implemented through the implementation of activities with a target these which are short and longer term. In the implementation of the CSR, there are various the judgment of the community. The response from the community as input for the firms could continue to make efforts to especially with regard to the application of more effective communications strategy. Keyword:   communications strategy, corporate social responsibility, the implementation of corporate social responsibility, the life quality of society